Evaluation of the Stress Level of Children with Idiopathic Scoliosis in relation to the Method of Treatment and Parameters of the Deformity. (31st July 2012) - Leszczewska, Justyna; Czaprowski, Dariusz; Pawłowska, Paulina; Kolwicz, Aleksandra; Kotwicki, Tomasz
Abstract : Stress level due to existing body deformity as well as to the treatment with a corrective brace is one of factors influencing the quality of life of children with idiopathic scoliosis undergoing non-surgical management. The purpose of the study was to evaluate the stress level among children suffering from idiopathic scoliosis in relation to the method of treatment and the parameters of the deformity. Seventy-three patients with idiopathic scoliosis participated in the study. Fifty-two children were treated by means of physiotherapy, while 21 patients were treated with both Cheneau corrective brace and physiotherapy. To assess the stress level related to the deformity itself and to the method of treatment with corrective brace, the two Bad Sobernheim Stress Questionnaires (BSSQs) were applied, the BSSQ Deformity and the BSSQ Brace, respectively.